Laporan Kasus: Laserasi Palpebrae Tertusuk Kawat - Razzaqy, Razzaqy; Hermadi, Hermadi; Dinata, M. Thoriq Satria; Negari, Ayu Rahajeng Dianing; Fatikhawati, Anandya; Ardiani, Khoiriya; Haniifah, Ulaa; Anas, Muhammad (Journal of Islamic Medicine, 2023)
BBackground: Eyelid laceration is a tear in the eyelid caused by sharp trauma. Sharp trauma to the eye is trauma that causes injury and affects the entire wall of the eyeball (cornea). Sharp trauma can happen anywhere and hit anyone. In children, it usually occurs due to tools from games that are commonly played, such as archery, catapults, air rifles, punctures from toy handles, and others. Case Report: Based on the case below, a female patient aged four years and eight months came with complaints of pain and bleeding from the left eyelid. The incident started with the tearing of the left eyelid due to being caught in the wire until it penetrated, and the mother tried to remove it. Conclusion: Sharp trauma to the eye is when the eye is penetrated by a sharp object or small object at high speed that penetrates the cornea or sclera. Sharp trauma can be diagnosed through inspection, in addition to history, physical examination, and support. Treatment that can be done is reconstruction.